MOOC RC design - Zuhan, Nurizaty; Saari, Nadiah; Oh, Chai Lian; Mohd Amin, Norliyati; Ismail, Rozaina (2025)
Reinforced Concrete (RC) Design is an educational innovation designed to enhance civil engineering subject by offering a flexible, globally accessible and industry-relevant course through an e-learning platform Massive Open Online Course (MOOC). This course focuses on the design of key RC building elements, i.e. slabs, beams, columns, shear walls and foundations, and delivered through structured modules aligned with Malaysia UBBL and Eurocodes. RC Design supports lifelong learning and improves students’ competency by integrating interactive and outcome-based learning methods. This course features comprehensive assessments comprising of design assignment, project and online tests to strengthen critical thinking and practical application. Special features include virtual site visits to connect theory with real-world practice, gamified quizzes to enhance engagement and the application of design software to expose learners to digital tools utilised in the industry. Original teaching videos, real-world design cases and forums for instructor-student interaction enhance the overall learning experience. RC Design was developed using a systematic instructional design approach, implemented with clear learning outcomes and interactive content and monitored via learner engagement data and surveys. Feedback shows strong satisfaction: 70% of learners find this course beneficial and about 90% of respondents cite its effectiveness. This innovation supports the Malaysia Education Blueprint 2015–2025 and Sustainable Development Goal 4 (Quality Education) by ensuring equitable access to technical education and promoting lifelong learning through digital transformation in engineering education. RC Design not only bridges the education gap but also re-defines how future engineers are prepared for complex problem-solving in the digital era.